Dietary Observations of Ultra-Endurance Runners in Preparation for and During a Continuous 24-h Event - Kinrade, Emma J.; Galloway, Stuart D. R. (Frontiers in Physiology, 2021)
Carbohydrate (CHO) intake recommendations for events lasting longer than 3 hours indicate that athletes should ingest up to 90g.hr-1 of multiple transportable carbohydrates. We examined the dietary intake of amateur (males: n=11, females: n=7) ultra-endurance runners (mean age and mass 41.5 ± 5.1 years and 75.8 ± 11.7 kg) prior to, and during a 24-hour ultra-endurance event. Heart rate and interstitial glucose concentration (indwelling sensor) were also tracked throughout the event. Pre-race diet (each 24h over 48h) was recorded via weighed intake and included the pre-race meal (1-4hrs pre-race). In-race diet (24hr event) was recorded continuously, in-field, by the research team. Analysis revealed that runners did not meet the majority of CHO intake recommendations. CHO intake over 24-48h pre-race was lower than recommended (4.0±1.4g·kg-1; 42 ± 9% of total energy), although pre-race meal CHO intake was within recommended levels (1.5±0.7g·kg-1). In-race CHO intake was only in the 30-60g·h-1 range (mean intake 33±12g·h-1) with suboptimal amounts of multiple transportable CHO consumed. Exercise intensity was low to moderate (mean 68%HRmax 45%VO2max) meaning that there would still be an absolute requirement for CHO to perform optimally in this ultra-event. Indeed, strong to moderate positive correlations were observed between distance covered and both CHO and energy intake in each of the 3 diet periods studied. Independent t-tests showed significantly different distances achieved by runners consuming ≥5 vs <5g·kg-1 CHO in pre-race diet (98.5±18.7 miles (158.5±30.1 km) vs 78.0±13.5 miles (125.5±21.7 km), p=0.04) and ≥40 vs <40g·h-1 CHO in-race (92.2±13.9 miles (148.4±22.4 km) v 74.7±13.5 miles (120.2±21.7 km), p=0.02). Pre-race CHO intake was positively associated with ultra-running experience, but no association was found between ultra-running experience and race distance. No association was observed between mean interstitial glucose and dietary intake, or with race distance. Further research should explore approaches to meeting pre-race dietary CHO intake as well as investigating strategies to boost in-race intake of multiple transportable CHO sources. In 24-hour ultra-runners, studies examining the performance enhancing benefits of getting closer to meeting pre-race and in-race carbohydrate recommendations are required.